Pengaruh Diklat, Komunikasi, dan Promosi Jabatan terhadap Kinerja Pegawai (Studi Kasus di BKPSDM Kabupaten Pidie Jaya) - Juliana, Fitria; Fauzi, Fauzi; Mirza, Mirza (Aceh Cooperative Care, 2025)
The study aims to analyze the influence of training, communication and job promotion on employee performance. The study was conducted on a sample of 48 employees of BKPSDM Pidie Jaya Regency. 2) communication has an effect on employee performance. With the type of associative research with a quantitative approach. Problem analysis is proven by the path analysis model. The results found that, 1) there is a causal relationship between training variables, communication and job promotion with a fairly strong category, which gives a positive contribution of 55.5% to employee performance. 2) The provision of training has a significant direct and indirect effect on employee performance of 47.5%, while the communication factor is 50.18% and the influence of job promotion is 47.21%.